Using Palliative Care Needs Rounds in the UK for care home staff and residents: an implementation science study - Liz Forbat; Aisha Macgregor; Karen Spilsbury; Brendan McCormack; Alasdair Rutherford; Barbara Hanratty; Jo Hockley; Lisa Davison; Margaret Ogden; Irene Soulsby; Maisie McKenzie (NIHR Journals Library, 2024)
Background Care home residents often lack access to end-of-life care from specialist palliative care providers. Palliative Care Needs Rounds, developed and tested in Australia, is a novel approach to addressing this. Objective To co-design and implement a scalable UK model of Needs Rounds. Design A pragmatic implementation study using the integrated Promoting Action on Research Implementation in Health Services framework. Setting Implementation was conducted in six case study sites (England, n = 4, and Scotland, n = 2) encompassing specialist palliative care service working with three to six care homes each. Participants Phase 1: interviews (n = 28 care home staff, specialist palliative care staff, relatives, primary care, acute care and allied health practitioners) and four workshops (n = 43 care home staff, clinicians and managers from specialist palliative care teams and patient and public involvement and engagement representatives). Phase 2: interviews (n = 58 care home and specialist palliative care staff); family questionnaire (n = 13 relatives); staff questionnaire (n = 171 care home staff); quality of death/dying questionnaire (n = 81); patient and public involvement and engagement evaluation interviews (n = 11); fidelity assessment (n = 14 Needs Rounds recordings). Interventions (1) Monthly hour-long discussions of residents' physical, psychosocial and spiritual needs, alongside case-based learning, (2) clinical work and (3) relative/multidisciplinary team meetings. Main outcome measures A programme theory describing what works for whom under what circumstances with UK Needs Rounds. Secondary outcomes focus on health service use and cost effectiveness, quality of death and dying, care home staff confidence and capability, and the use of patient and public involvement and engagement. Data sources Semistructured interviews and workshops with key stakeholders from the six sites; capability of adopting a palliative approach, quality of death and dying index, and Canadian Health Care Evaluation Project Lite questionnaires; recordings of Needs Rounds; care home data on resident demographics/health service use; assessments and interventions triggered by Needs Rounds; semistructured interviews with academic and patient and public involvement and engagement members. Results The programme theory: while care home staff experience workforce challenges such as high turnover, variable skills and confidence, Needs Rounds can provide care home and specialist palliative care staff the opportunity to collaborate during a protected time, to plan for residents' last months of life. Needs Rounds build care home staff confidence and can strengthen relationships and trust, while harnessing services' complementary expertise. Needs Rounds strengthen understandings of dying, symptom management, advance/anticipatory care planning and communication. This can improve resident care, enabling residents to be cared for and die in their preferred place, and may benefit relatives by increasing their confidence in care quality. Limitations COVID-19 restricted intervention and data collection. Due to an insufficient sample size, it was not possible to conduct a cost-benefit analysis of Needs Rounds or calculate the treatment effect or family perceptions of care. Conclusions Our work suggests that Needs Rounds can improve the quality of life and death for care home residents, by enhancing staff skills and confidence, including symptom management, communications with general practitioners and relatives, and strengthen relationships between care home and specialist palliative care staff. Future work Conduct analysis of costs-benefits and treatment effects. Engagement with commissioners and policy-makers could examine integration of Needs Rounds into care homes and primary care across the UK to ensure equitable access to specialist care. Study registration This study is registered as ISRCTN15863801. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR128799) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 19. See the NIHR Funding and Awards website for further award information. Plain language summary Care home residents often lack access to end-of-life care from hospice teams and so may experience distressing symptoms at end of life if care home staff cannot fully meet their needs. We examined how an approach which worked well in Australia called 'Palliative Care Needs Rounds' (or 'Needs Rounds') could be used in the United Kingdom. We interviewed 28 people (care home staff, hospice staff and other National Health Service/social care professionals in the community) about their understanding of the United Kingdom setting, what might help trigger change and what results they would want. We discussed these interviews at online workshops with 43 people, where we started to develop a theory of 'what would work, for whom, under what circumstances' and determine what United Kingdom Needs Rounds would look like. Six specialist palliative care services, each partnered with three to six local care homes, used Needs Rounds for a year. We collected information on care home residents, staff experiences of using Needs Rounds, relatives' perceptions of care quality, staff views of residents' quality of death, and on their ability to provide a palliative approach to residents. We found that Needs Rounds can provide care home staff and specialist palliative care staff the opportunity to work together during a protected time, to plan for residents' last months of life. Needs Rounds build care home staff confidence and can strengthen relationships and trust, while using each services' expertise. Needs Rounds strengthen understandings of dying, symptom management, advance/anticipatory care planning and communication between care home staff, families, specialist palliative care staff and primary care. This improves the quality of resident care, enabling residents to be cared for and die in their preferred place, and also benefits relatives by increasing their confidence in care quality. Scientific summary Background Despite high levels of morbidity and mortality, care home (CH) residents do not always have adequate access to specialist palliative care (SPC). Residents can experience uncontrolled symptoms, poor-quality deaths and futile/burdensome hospitalisations. CH staff can feel unprepared and unsupported to look after residents at end of life. Although models exist for improving end-of-life care in CHs, these are primarily focused on education and do not adequately triage residents to focus on those most at risk of dying without a plan in place and rarely integrate clinical care. A clinical innovation in Australia called 'Palliative Care Needs Rounds' (hereafter 'Needs Rounds') combines triaging, with anticipatory person-centred planning, case-based learning and case conferencing. The approach has been synthesised into a checklist to provide guidance to clinicians running Needs Rounds. In Australia, Needs Rounds reduced length of stay in hospital and number of admissions, increased dying in preferred place, improved symptoms at end of life and normalised death/dying to CH staff. CH staff felt more confident looking after the residents. Preventing hospital admissions saved AUD$1.7 million over a year (nearly £1 million). Aim To co-design and implement a scalable UK model of Needs Rounds, which takes account of the different policy/practice context in the UK. Objectives The implementation objectives were to: co-design a UK version of Needs Rounds, which is responsive to different contextual characteristics of the UK CH sector (Phase 1) implement the adapted model of care, assess feasibility, acceptability and effectiveness and ultimately propose how the model of care can be further refined and adopted in the UK context, to reap the benefits demonstrated in the Australian work (Phase 2).